El imperativo de movilidad y los procesos de precarización en Educación Superior. Docentes e investigadores españoles entre Ecuador y España - GÓMEZ, Carmen; VEGA, Cristina (Revista Iberoamericana de Estudios de Desarrollo)
The new mobilities of the Spanish are inextricably linked to the crisis and the way it impacts on Higher Education. In the last decade, Latin America has been a leading destination for qualified young people who have been inserted into university systems in the region attracted by educational reforms and demand for graduate degrees. In the article the keys to such insertion within the framework of an unequal knowledge economy on a global scale, questioning the implications of the imperative of mobility that today has been elevated to a requirement of the academic career, are analysed. The latter only conceals a form of precariousness that is prolonged over time, subject to the social, economic and political swings chained in the countries of origin, destination and transit. This is the case of Ecuador, which has gone from being a receiving country for university graduates to presenting a scenario of incorporation and uncertain permanence. This gives rise to different responses, among them, the return to Spain, the displacement to new destinations and the insertion in other labour or training activities in Ecuador. Based on a survey and in-depth interviews with Spaniards at Ecuadorian universities, as well as data from the Ecuadorian higher education system, the inequalities that arise in these mobilities, the role played by university policies and the dynamics of crisis, are analysed in the article. That condition the displacements.